Diagnostic accuracy of transvaginal ultrasound for detection of endometriosis using International Deep Endometriosis Analysis (IDEA) approach: prospective international pilot study. (1st September 2022) - Leonardi, M.; Uzuner, C.; Mestdagh, W.; Lu, C.; Guerriero, S.; Zajicek, M.; Dueckelmann, A.; Filippi, F.; Buonomo, F.; Pascual, M. A.; Stepniewska, A.; Ceccaroni, M.; et al.
ABSTRACT: Objective: To evaluate the diagnostic accuracy of transvaginal ultrasound (TVS) in predicting deep endometriosis (DE) following the International Deep Endometriosis Analysis (IDEA) consensus methodology. Methods: This was an international multicenter prospective diagnostic accuracy study involving eight centers across six countries (August 2018–November 2019). Consecutive participants with endometriosis suspected based on clinical symptoms or historical diagnosis of endometriosis were included. The index test was TVS performed preoperatively in accordance with the IDEA consensus statement. At each center, the index test was interpreted by a single sonologist. Reference standards were: (1) direct visualization of endometriosis at laparoscopy, as determined by a non‐blinded surgeon with expertise in endometriosis surgery; and (2) histological assessment of biopsied/excised tissue. Surgery was performed within 12 months following the index TVS. Accuracy, sensitivity, specificity, positive and negative predictive values (PPV and NPV) and positive and negative likelihood ratios (LR+ and LR–) of TVS in the diagnosis of DE were calculated. Results: Included in the study were 273 participants with complete clinical, TVS, laparoscopic and histological data. Of these, based on histology, 256 (93.8%) were confirmed to have endometriosis, including superficial endometriosis, and 190 (69.6%) were confirmed to have DE. Based on surgical visualization, 207/273 (75.8%) patients had DE. For DE overall, the diagnostic performance of TVS based on surgical visualization as the reference standard was as follows: accuracy, 86.1%; sensitivity, 88.4%; specificity, 78.8%; PPV, 92.9%; NPV, 68.4%; LR+, 4.17; LR–, 0.15, and the diagnostic performance of TVS based on histology as the reference standard was as follows: accuracy, 85.9%; sensitivity, 89.8%; specificity, 75.9%; PPV, 90.4%; NPV, 74.6%; LR+, 3.72; LR–, 0.13. Conclusions: Using the IDEA consensus methodology provides strong diagnostic accuracy for TVS assessment of DE. We found a higher TVS detection rate of DE overall than that reported by the most recent meta‐analysis on the topic (sensitivity, 79%), albeit with a lower specificity. © 2022 International Society of Ultrasound in Obstetrics and Gynecology.